2021
DOI: 10.1038/s41467-021-25086-5
|View full text |Cite
|
Sign up to set email alerts
|

Inferring multilayer interactome networks shaping phenotypic plasticity and evolution

Abstract: Phenotypic plasticity represents a capacity by which the organism changes its phenotypes in response to environmental stimuli. Despite its pivotal role in adaptive evolution, how phenotypic plasticity is genetically controlled remains elusive. Here, we develop a unified framework for coalescing all single nucleotide polymorphisms (SNPs) from a genome-wide association study (GWAS) into a quantitative graph. This framework integrates functional genetic mapping, evolutionary game theory, and predator-prey theory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 115 publications
0
15
0
Order By: Relevance
“…Recently, a framework has been proposed to study the genetic basis of phenotypic plasticity and highlights quantitative genetics and gene hub approaches ( Laitinen and Nikoloski, 2019 ). Furthermore, approaches have been developed that integrate genetic mapping, evolutionary game theory and predator–prey theory ( Yang et al , 2021 ).…”
Section: Approaches Considerations and Promising Research Directions ...mentioning
confidence: 99%
“…Recently, a framework has been proposed to study the genetic basis of phenotypic plasticity and highlights quantitative genetics and gene hub approaches ( Laitinen and Nikoloski, 2019 ). Furthermore, approaches have been developed that integrate genetic mapping, evolutionary game theory and predator–prey theory ( Yang et al , 2021 ).…”
Section: Approaches Considerations and Promising Research Directions ...mentioning
confidence: 99%
“…85 More recently, Yang and coworkers proposed that the interaction between iminiums generated from allenamides and the catalyst is ionic. 86 However, theoretical work suggested that double coordination modes are much more likely. 53,67 Accordingly, we considered that the mechanism could also proceed through establishing two H-bonding interactions between the chiral phosphate and the reactants.…”
Section: Phosphate-catalyzed Reactions Involving Allenamidesmentioning
confidence: 99%
“…reported the enantioselective addition of -alkynyl ketones to allenamides. 86 Using our previous computational work on this reaction class, we can confidently analyze the steric demands on the nucleophile and determine that sp 3 substituents will likely be bulkier than sp 2 and sp substituents. Accordingly, we can expect the nucleophile will fit into the chiral pocket similar to that shown for model 3.…”
Section: Comprehensive Qualitative Modelsmentioning
confidence: 99%
“…Epistasis was suggested as an explanation of missing heritability [19]. The idea of epistasis was extended in the omnigenic theory, which states that complex traits are controlled by all genes of the organism [20].…”
Section: The Growing Need In Functional Knowledge For Crop Improvementmentioning
confidence: 99%
“…Increasing the number of lines by a factor of 10-100 would be a difficult task. In another work, the number of samples for determining the interaction of only two genes using GWAS is estimated at 10,000 while there are millions of millions of gene pairs [20]. It can be summarized that currently, we do not have adequate tools to comprehensively evaluate the epistasis [21].…”
Section: The Growing Need In Functional Knowledge For Crop Improvementmentioning
confidence: 99%